PENEGAKAN HUKUM TERHADAP PELAKU PELANGGARAN LALU LINTAS YANG MENGAKIBATKAN KORBAN MENINGGAL DUNIA DI WILAYAH HUKUM POLRESTA JAMBI - Muhammad Badri; Masriyani Masriyani; Islah Islah (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
Traffic violations are the problem causes the majority of traffic accidents. Mainly because of the human factor that road users do not obey traffic rules, police have been carrying out various efforts, both preventive repressive through socialization to society and give blangko fines speeding tickets and persuasive manner through educational outreach to the public about traffic laws in perspective of legislation, traffic and road transport is regulated in Act No. 22 of 2009 about traffic and Road Transport (hereinafter referred to as the traffic laws and Road Transport). In the Traffic laws and Road Transport, among other organized effort of coaching, prevention and law enforcement in the field of road transport and traffic. The coaching efforts made through an increase in the intensity of traffic education and extension of law and the construction of human resources. Due to traffic accidents besides inflicting casualties and property losses also financially/materially, as the amount of losses in natural by riders. It is concerned, if not done strategic steps to enhance safety and compliance with traffic laws of society, then it will add to the long list of casualties and losses are material.Keyword : law enforcement, traffic